Hydrops fetalis associated with SARS-CoV-2 placentitis and de novo CDK13 mutation: an integrated genetic and histological analysis - Zanin, Valentina; Piccinin, Giada; Faletra, Flavio; Mio, Catia; Angelini, Marta; Orsaria, Maria; Pittini, Carla; Driul, Lorenza (Acta Biomedica Atenei Parmensis, 2025)
We present a case of a 33-year-old woman with a diagnosis of hydrops fetalis at 33 weeks gestation. The histopathological examination of the placenta deposes for SARS-CoV-2 placentitis and genetic analysis reveals evidence of a de novo heterozygous mutation of the CDK13 mutation gene in the newborn. This report presents a case of COVID-19 during pregnancy associated with SARS-CoV-2 placentitis and highlights the characteristic histopathology of this recently described condition, which can lead to hydrops. On the other hand, this is the first reported case of hydrops fetalis in a fetus carrier of a pathogenic CDK13 gene variant. Moreover, since the reported patients with CDK13 mutations and prenatal complications we cannot exclude the causality or at least the contribution of this variant in generating the hydrops